Effects of rugby wheelchair design on output velocity and acceleration - Usama-Alvarez, C. C.; Fuss, F. K.; Subic, A. (Procedia Engineering, 2011)
The effects of specific wheelchair design parameters on performance improvement in wheelchair rugby in particular have not been described nor defined in research literature to date. The interaction between the wheelchair and the athlete is difficult to comprehend. With the aim of exploring the influence of wheelchair design variations on acceleration and velocity values for wheelchair rugby athletes, RMIT University research team has developed a purpose-built fully adjustable wheelchair frame for use with a wheelchair ergometer. These two instruments used in conjunction, allow valid and reliable data collection in controlled experiments. This paper presents a case study describing a novel method developed for quantitative analysis of the effects of variations of vertical and horizontal seat, and wheelchair camber angle on the performance of an elite athlete during wheelchair propulsion on a static ergometer.